2019
DOI: 10.3390/ijms20184496
|View full text |Cite
|
Sign up to set email alerts
|

Immunomorphological Pattern of Molecular Chaperones in Normal and Pathological Thyroid Tissues and Circulating Exosomes: Potential Use in Clinics

Abstract: The thyroid is a major component of the endocrine system and its pathology can cause serious diseases, e.g., papillary carcinoma (PC). However, the carcinogenic mechanisms are poorly understood and clinical useful biomarkers are scarce. Therefore, we determined if there are quantitative patterns of molecular chaperones in the tumor tissue and circulating exosomes that may be useful in diagnosis and provide clues on their participation in carcinogenesis. Hsp27, Hsp60, Hsp70, and Hsp90 were quantified by immunoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 39 publications
1
37
0
1
Order By: Relevance
“…The level of Hsp27 was high but did not show a significant quantitative variation in cancerous tissues compared to the corresponding normal parenchyma, whereas Hsp60, Hsp70, and Hsp90 were increased in FTC compared to FA and/or to adjacent normal parenchyma [22]. In another study, the immunohistochemical levels of Hsp27, Hsp60, and Hsp90, but not Hsp70, were high in PTC as compared with benign goiters and normal peritumoral tissues [21]. Both works also reported the intracellular distribution of each Hsp, showing not only an increased level in cancerous compared to normal tissues, but also an altered localization, with accumulation in the cytoplasm and plasma cell membrane in cancerous specimens [21,22].…”
Section: Various Chaperones Assessed Simultaneouslymentioning
confidence: 88%
See 1 more Smart Citation
“…The level of Hsp27 was high but did not show a significant quantitative variation in cancerous tissues compared to the corresponding normal parenchyma, whereas Hsp60, Hsp70, and Hsp90 were increased in FTC compared to FA and/or to adjacent normal parenchyma [22]. In another study, the immunohistochemical levels of Hsp27, Hsp60, and Hsp90, but not Hsp70, were high in PTC as compared with benign goiters and normal peritumoral tissues [21]. Both works also reported the intracellular distribution of each Hsp, showing not only an increased level in cancerous compared to normal tissues, but also an altered localization, with accumulation in the cytoplasm and plasma cell membrane in cancerous specimens [21,22].…”
Section: Various Chaperones Assessed Simultaneouslymentioning
confidence: 88%
“…In another study, the immunohistochemical levels of Hsp27, Hsp60, and Hsp90, but not Hsp70, were high in PTC as compared with benign goiters and normal peritumoral tissues [21]. Both works also reported the intracellular distribution of each Hsp, showing not only an increased level in cancerous compared to normal tissues, but also an altered localization, with accumulation in the cytoplasm and plasma cell membrane in cancerous specimens [21,22]. These results agree with other works showing a change in the cellular distribution or even extracellular secretion of Hsps during carcinogenesis processes [61][62][63][64][65].…”
Section: Various Chaperones Assessed Simultaneouslymentioning
confidence: 91%
“…Caruso et al found that the levels of Hsp27, Hsp60, and Hsp90 were increased in TPC tissue compared with normal peritumoral tissue and benign goiters. The levels of HSPs in the exosomes of patients with TPC before surgery were significantly higher than those in the exosomes from the same patients after surgery and from patients with benign goiters (122). TC is considered one of the most immunogenic cancers (123); thus, the rapid development of immunotherapy and exosomes as a delivery system brings new opportunities for the treatment of TC.…”
Section: Exosomes Mediate the Immune Regulation Of Tcmentioning
confidence: 97%
“…Moreover, patients with metastatic PTC have significantly higher levels of circulating exosomal miRNAs and hypoxic PTC cells can secrete exosomes that modulate the expression of TGF-β and collagen isoforms, enhancing the tumoral angiogenesis [ 192 ]. The exosomes secreted by CSCs also modulate the polarization of TAMs toward the M2 phenotype and suppress NK cell activity, promoting an immunosuppressive environment in CSC niches [ 193 , 194 , 195 , 196 ]. In turn, CAFs and TAMs also release exosomes that contribute to the regulation of the TME [ 187 , 197 , 198 ].…”
Section: Tumor Microenvironment and Csc Maintenancementioning
confidence: 99%